Based on the RADIUS and AAA Authentication of the Campus Networks Security System Design and Implementation - Yuyang Lu; Xiang Zhang Chen; Wenjie Wang; Yong Yang (Institute of Advanced Engineering and Science, 2014)
As the work of digital campus construction, the function of network become more and more important . The kernel of digital campus is fast speed, function formidable, resource widely. The campus network is a special network ,which face special user community ,it is thought ,technology of active, and it adopt access layer access ,so the network security is lower, Vulnerable to illegal users and virus attacks. This text use RADIUS and AAA authentication technology in the campus, through user authentication, strengthen the network access restrictions, the log service, campus network management more systematic and safe. DOI : http://dx.doi.org/10.11591/telkomnika.v12i4.4776